COMMUNITY-BASED ENTREPRENEURSHIP AND LOCAL ECONOMIC RESILIENCE: A CONCEPTUAL FRAMEWORK FOR INCLUSIVE MSME DEVELOPMENT - Rama Tresnadi; Lili Adi Wibowo (Journal of Jabar Economic Society Networking Forum, 2024)
This conceptual paper develops an integrative framework for community-based entrepreneurship in micro, small, and medium enterprises (MSMEs). The analysis connects the resource-based view, dynamic capabilities, absorptive capacity, organizational learning, social capital, open innovation, resilience, and entrepreneurial-ecosystem perspectives. It does not claim primary survey, interview, experimental, or statistical data. The synthesis argues that community participation, local knowledge, enterprise networks, and institutional support should be organized as repeatable managerial routines rather than treated as isolated interventions. The framework proposes staged diagnosis, implementation, evaluation, and learning mechanisms and identifies implications for owner-managers, support organizations, and future empirical research.